2020
DOI: 10.1017/s0007114520000616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of standard v. very long Roux limb Roux-en-Y gastric bypass on nutrient status: a 1-year follow-up report from the Dutch Common Channel Trial (DUCATI) Study

Abstract: Laparoscopic Roux-en-Y gastric bypass (RYGB) is considered the ‘gold standard’ for surgical treatment of morbid obesity. It is hypothesised that reducing the length of the common limb positively affects the magnitude and preservation of weight loss but may also impose a risk of malnutrition. The aim of this study was to compare patients’ nutrient and vitamin deficiencies in standard RYGB with a very long Roux limb RYGB (VLRL-RYGB). This study was part of the multicentre randomised controlled trial (Dutch Commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
12
0
3
Order By: Relevance
“…A shorter common channel may have resulted in greater weight loss, but probably with a risk of severe malabsorption, as previously shown for distal RYGB 29 . The Dutch DUCATI randomized trial 30 , 31 of standard versus distal RYGB with a common channel of 100 cm may shed further light on this.…”
Section: Discussionmentioning
confidence: 99%
“…A shorter common channel may have resulted in greater weight loss, but probably with a risk of severe malabsorption, as previously shown for distal RYGB 29 . The Dutch DUCATI randomized trial 30 , 31 of standard versus distal RYGB with a common channel of 100 cm may shed further light on this.…”
Section: Discussionmentioning
confidence: 99%
“…However, these surgical procedures also carry risks of increased morbidity and mortality [11,12]. In addition, one side effect of surgical procedures that aim to reduce nutrient absorption is impaired availability of essential micronutrients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This would make dietary sources of these longer chain PUFAs even more important. Since essential nutrient deficiency following malabsorptive bariatric operations is common [13,14], we sought to investigate the effects of DJBL therapy on circulating concentrations of EFAs and other bioactive PUFAs. We hypothesised that circulating concentrations of these fatty acids would be lower after DJBL treatment than following an alternative weight loss intervention that did not involve restricting nutrient absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a higher intake of potassium provided by fruits and vegetables may also be of help due to the alkaline load [97]. According to Leeman et al [98], potassium deficiency is very frequent after RYGB procedures, and a recent study showed a decrease of 45.6% on fiber intake after RYGB, reflecting the smaller amount of plant-based food consumption (fruits, vegetables, cereals and legumes), which corresponds to the main source of potassium [99]. Albeit there is no specific recommendation on potassium intake after BS, the RDA for adults is of 120 mEq/day [100].…”
Section: Citrate and Potassiummentioning
confidence: 99%